2006
DOI: 10.1021/ja0626180
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Absolute Stereochemical Assignment of (+)- and (−)-Galbulimima Alkaloid 13

Abstract: We describe the total synthesis of (+)- and (-)-galbulimima alkaloid 13. The absolute stereochemistry of natural (-)-galbulimima alkaloid 13 is revised to 2S. Sequential use of catalytic cross-coupling and cross-metathesis reactions followed by an intramolecular Diels-Alder reaction provided the required trans-decalin AB-ring system and masked the C16 carbonyl as an N-vinyl carbamate for late-stage unveiling in the form of the necessary C16 enone. A vinyl radical cyclization secured the C-ring, while successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 28 publications
4
65
0
2
Order By: Relevance
“…[5] Motivated by the efficiency of the transient-d-imino ketone strategy that we employed [6] for the introduction of the CDE ring system of class II and class III galbulimima alkaloids [7] (Scheme 2), we sought to develop a new formal [3+3] cycloaddition reaction.…”
Section: Mohammad Movassaghi* and Bin Chenmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Motivated by the efficiency of the transient-d-imino ketone strategy that we employed [6] for the introduction of the CDE ring system of class II and class III galbulimima alkaloids [7] (Scheme 2), we sought to develop a new formal [3+3] cycloaddition reaction.…”
Section: Mohammad Movassaghi* and Bin Chenmentioning
confidence: 99%
“…The stereoselective formation of tricycles 11 a-c via the corresponding imino ketones 7 a-c is consistent with our proposed biogenesis of this substructure in the galbulimima alkaloids. [6] The use of iminium chloride 5 b [9] Scheme 1. Formal [3+3] cycloaddition reaction.…”
Section: Mohammad Movassaghi* and Bin Chenmentioning
confidence: 99%
“…Sharpless et al as well as the Meldal research group independently employed the use of copper(I) catalysis in the formation of a cyclic adduct during azide-alkyne cycloaddition reactions [33,34]. In the synthesis of (−)-galbulimima alkaloid, the Movassaghi research group reported the use of copper-inspired coupling of vinyl bromide and oxazolidinone as one of its key intermediate steps [35]. A similar strategy was also employed in the synthesis of himandrine alkaloid [36].…”
Section: Introductionmentioning
confidence: 99%
“…After completion of the reaction, the mixture was allowed to cool at the room temperature, and the crude product was extracted into CH 2 Cl 2 . The removal of the solvent using rotary evaporator under reduced pressure and flash column chromatography using CH 2 …”
Section: Methodsmentioning
confidence: 99%
“…N-Vinyl analogues are widely used as very important intermediates in polymerizations, 1 alkaloid syntheses, 2 protecting procedure 3 , Diels-Alder reactions 4 , regioselective Heck couplings 5 and pyrimidine syntheses. 6 Whereas numerous reaction methods for the preparation of N-vinyl analogues have been previously reported using dehydration, 7 dehydroalkoxylation, 8 copper 9 and palladium 10 catalyzed vinylation, coupling with 2-halo vinyliodides, 11 and decomposition of acyloxy ethyl derivatives, 12 introducing vinyl moieties at the nitrogen atom in lactams have not been generally studied.…”
Section: Introductionmentioning
confidence: 99%